The characterization of human oral mucosal fibroblasts and their use as feeder cells in cultivated epithelial sheets. (6th September 2017) - Higa, Kazunari; Satake, Yoshiyuki; Shimazaki, Jun
Aim: To characterize human oral mucosa middle interstitial tissue fibroblasts (hOMFs) and their application in the cultivation of epithelial sheets.Methodology: hOMFs were cultured with methylcellulose to form cell clusters. hOMFs amplified in adhesive culture were analyzed by flow cytometry, and were found to differentiate into multiple cell types suitable for the cultivation of human corneal epithelial sheets. hOMFs were expanded from clusters to analyze CD56 and PDGFRα expression.Results: These cells showed similar differentiation patterns as keratocytes, and similar expression patterns as mesenchymal and neural cells. Furthermore, we established human corneal epithelial sheets using hOMFs.Conclusion: hOMFs may be of neural crest origin and possess multipotent differentiation capacity, and are suitable for use as an autologous cell source for corneal regeneration. Lay abstract: Mesenchymal stem cells can be found in the middle interstitial tissue just under the human oral mucosa epithelium. To mediate the application of these mucosal stem cells, called human oral mucosa middle interstitial tissue fibroblasts (hOMFs), in a clinical setting, their characteristics were analyzed to determine whether they can differentiate into corneal stroma cells called keratocytes and develop human corneal limbal epithelial sheets by coculture with hOMFs as feeder cells as a substitute for 3T3 feeder cells from mice. hOMFs show potential as a new cellular source for autologous regeneration of mesenchymal or neural crest-derived tissues.